Strength and stiffness of concrete with recycled concrete aggregates. (15th November 2017) - McGinnis, Michael J.; Davis, Mark; de la Rosa, Andres; Weldon, Brad D.; Kurama, Yahya C.
Highlights: Regional variability in RCA and RAC properties was investigated across a wide range. Strength of RAC decreased 16.6% at 50% replacement and 26.4% at 100% replacement. Stiffness of RAC decreased 26.4% at 50% replacement and 34.4% at 100% replacement. RCA absorption and deleterious material were primary strength/stiffness predictors. Coarse aggregate gradation impacted RAC similarly to impacts noted for NA concrete. Abstract: By crushing old concrete to make recycled concrete aggregates (RCA) for use in new concrete, the overall environmental impacts of concrete are reduced. However, a better understanding of the use of RCA in new concrete is necessary before adoption in structural concrete applications can be widely realized. In particular, the strength, stiffness (Modulus of Elasticity), workability, and durability of concrete using RCA can be different than concrete that uses natural aggregate (NA). Variability in RCA properties from source to source also must be addressed if guidelines for RCA use are to be adopted. This paper describes properties of RCA and recycled aggregate concrete (RAC) with materials from four distinct areas of the United States (Northeast, South, Midwest and Southwest regions), making this study the most geographically varied study of RCA known. Variability in aggregate properties and the relationships between them are addressed within the paper. Equations allowing concrete mix designers to predict strength and stiffness of mixes are shown to be applicable across a much broader range of RCA properties than previously known. Similarly to concrete with natural aggregates, the strength and stiffness of RAC is shown to be impacted by the gradation of the coarse aggregates – smaller aggregates make stronger, stiffer concrete.